Positioning accuracy in optical trap assisted nanostructuring - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Paulus, Jan; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
The well-known optical diffraction limit prevents laser radiation from being focused to arbitrary small spots. Utilizing spherical micro-particles as near-field lenses provides an easy and robust way to overcome this limitation and to generate nanoscale surface structures. To achieve this, microspheres are positioned and translated with an optical trap and then used to focus pulsed laser radiation. The paper at hand presents the factors which influence the positioning accuracy in optical trap assisted nanostructuring. Theoretical considerations are backed up with experimentally obtained values of the surface structure accuracy in dependence of optical trap stiffness and particle position.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Direct-write; Nanostructuring; Optical trap; Ultrafast lasers